Vitamin D status after a high dose of cholecalciferol in healthy and burn subjects. Issue 5 (August 2015) - Rousseau, Anne-Françoise; Damas, Pierre; Ledoux, Didier; Lukas, Pierre; Carlisi, Agnès; Le Goff, Caroline; Gadisseur, Romy; Cavalier, Etienne
Highlights Levels of 25OH-D at hospital admission following burn were straightaway lower than our healthy subjects. Efficacy of 100, 000 IU cholecalciferol to raise 25OH-D levels (and free 25OH-D levels) was quite uncertain, lower or even zero, in burn patients when compared to healthy subjects. Higher cholecalciferol doses than general recommendations should probably be considered during acute burn care. Interest of free 25OH-D is still questionable.